Integrating Habituation Methods into Students’ Religious Character Education: A Qualitative Inquiry at SMKN 1 Ciamis, West Java - Saepul Milah; Syihabuddin Syihabuddin; Momod Abdul Somad; Mupid Hidayat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
In the face of moral decline and the impact of digital culture, enhancing religious character has emerged as a paramount objective in vocational education. Theoretical techniques in the classroom are frequently ineffective without regular practice. This study seeks to investigate the incorporation of habit-forming techniques to develop students' religious character at SMKN 1 Ciamis, West Java. This research employs a qualitative methodology. Data were gathered through observation, comprehensive interviews with the principal, Islamic Education instructors, and students, and documentation analysis. Data analysis was performed via data reduction, data presentation, and conclusion formulation utilizing source triangulation methods. The findings indicated that the incorporation of habit formation techniques was executed through three categories of habits: (1) spiritual habits, (2) social habits, and (3) environmental and health-related habits. Systematic school rules and oversight facilitated this integration. Habituation techniques have proven effective in transforming religious beliefs from mere cognition into observable behavior. The efficacy of this program is significantly dependent on the uniformity of the school environment and on educators' and students' collaboration in fostering a religious ambiance.